Solar pumps automation system using programmable logic controller for pumped hydro storage - Syafii, Syafii; Azizah, Farah; Salfikri, Iqbal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Pumped hydro storage (PHS) is an energy storage technology that uses electrical energy to pump water to a higher reservoir. The water is then released back into the lower reservoir to generate electricity. If the water source is limited, the pump must be stopped to prevent damage. The automation system can improve the pump's performance and protect it from damage. Therefore, a Solar pumps automation system using a programmable logic controller for pumped hydro storage is developed to avoid damage due to overheating that can damage the pump. With this automation system, the pump will automatically stop working when no water flows. The automation system at PHS will use a programmable logic controller or PLC as the controller, with a water flow sensor and an ultrasonic sensor to measure water levels. Arduino will assist in reading the analogue input on the PLC. The research shows that all the sensors work well with an error under 0.4%. The pump will turn on when the water level is less than 30 cm, while the pump will turn off when the water flow is less than 20 liters/minute. The pump can flow water stably at a water flow value level of 25-26 liters/minute.